(untitled) (Research, Society and Development, 2021)
World industrialization has been growing on a large scale, thereby causing the global energy demand to increase as well. That said, in order to have more energy available, much more will be required from the environment. Because some energy-using techniques are extremely aggressive to the ecosystem, renewable energy sources play a major role compared to the effects of energy generation and their relationship to other energy sources. Biomass has received much attention from the media and political leaders, both regarding alternative fuel sources and a way to minimize dependence on raw material imports from developed countries. This research uses a modelling method using CH4 Biogas Simulator comparatives for multi-variable evaluation in order to determine the regression equation, thus obtaining the amount of crude biogas and electrical energy that can be generated using biogas from cattle manure, pigs and poultry by means of biodigesters. The generated equation is easy to apply and evolve in model Y= 1.572731 + 0.985985 x cattle + 0.191372 x pigs + 0.021287 x birds with (r= 0.99) and is therefore suitable for estimating the potential value of biogas.